2011
DOI: 10.1371/journal.pone.0021480
|View full text |Cite
|
Sign up to set email alerts
|

Nanovesicles from Malassezia sympodialis and Host Exosomes Induce Cytokine Responses – Novel Mechanisms for Host-Microbe Interactions in Atopic Eczema

Abstract: BackgroundIntercellular communication can occur via the release of membrane vesicles. Exosomes are nanovesicles released from the endosomal compartment of cells. Depending on their cell of origin and their cargo they can exert different immunoregulatory functions. Recently, fungi were found to produce extracellular vesicles that can influence host-microbe interactions. The yeast Malassezia sympodialis which belongs to our normal cutaneous microbial flora elicits specific IgE- and T-cell reactivity in approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(144 citation statements)
references
References 50 publications
(70 reference statements)
6
135
1
2
Order By: Relevance
“…Exosome-like vesicles have been isolated and purified following specific and validated protocols used for a wide range of organisms and systems (Simpson et al 2009;Mathivanan et al 2010;Gehrmann et al 2011;Lasser et al 2012). Moreover, we reveal the size and shape of these structures, demonstrating the structures contain special excretory/secretory proteins, suggesting an important role for exosome-like vesicles in parasite-host communication, and modulate host cell immune responses.…”
Section: Discussionmentioning
confidence: 94%
“…Exosome-like vesicles have been isolated and purified following specific and validated protocols used for a wide range of organisms and systems (Simpson et al 2009;Mathivanan et al 2010;Gehrmann et al 2011;Lasser et al 2012). Moreover, we reveal the size and shape of these structures, demonstrating the structures contain special excretory/secretory proteins, suggesting an important role for exosome-like vesicles in parasite-host communication, and modulate host cell immune responses.…”
Section: Discussionmentioning
confidence: 94%
“…Secondly, nanovesicles and proteins from skin-colonising Malassezia spp. can induce the release of pro-inflammatory cytokines and histamine, which may contribute to the pathogenesis of AD (21,22). Thirdly, Malassezia spp.…”
Section: Discussionmentioning
confidence: 99%
“…The proposal that extracellular vesicle release is a general mechanism in distantly related fungi was supported by a recent study by Vallejo and coworkers [25], who demonstrated the occurrence of extracellular vesicles in Paracoccidiodes brasiliensis . A recent study by Gehrmann and colleagues [42] and unpublished results from our laboratory suggest that the basidiomycetes Malassezia sympodialis and Trichosporon asahii , respectively, also produces extracellular vesicles [ joffe ls, unpublished data ]. Although it is clear that the literature still requires confirmation of the production of extracellular vesicles by other species, this phenomenon has now been described for eight different fungal species.…”
Section: Characterization Of Extracellular Vesicle Production In Diffmentioning
confidence: 99%
“…Vesicle-stimulated macrophages also produced higher levels of TNF-α, IL-10 and TGF-β. In Malassezia sympodialis , release of extracellular vesicles inducing IL-4 and TNF-α has been described in patients with atopic eczema [42]. It remains unknown whether fungal extracellular vesicles are active during infection, but detection of released vesicles in both in vivo and in vitro models of infection supports this possibility [12].…”
Section: Are Extracellular Vesicles Involved In Interaction Of Fungi mentioning
confidence: 99%